Mengembangkan Kreativitas Anak Melalui Media Benang Warna pada Anak Usia Dini - Sagala, Devi Sinta; Br Hasibuan, Humaidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Creativity is the ability in a person to form and provide novelty in the form of ways, ideas and ideas that can benefit the person himself and the surrounding environment. Independent nature, skills and also the ability to solve problems are emphasized in children's creativity. The formulation of the research problem this time is